Resistance of Pinus banksiana to the European race of Gremmeniella abietina - Laflamme, G.; Blais, R. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
In the early 1980s, more than 90% of mortality caused by Gremmeniella abietina, European race, was recorded in red pine (Pinus resinosa) plantations 200 km northwest of Montreal, Quebec, Canada. Surrounding jack pines (Pinus banksiana) did not appear to be affected. Consequently, foresters began to plant the affected areas with jack pine seedlings. In 1988, plots of 100 jack pines were established in three of the four selected plantations. As reference, red pine seedlings were planted in 1989 under similar conditions in the fourth plantation. Observations were carried out annually from 1989 to 1992. Mortality of red pine seedlings reached 70% in 1992 while all jack pines on the three experimental sites were free of the disease except for a tip blight, a distinctive feature allowing race identification in the field. The North American race symptoms were present at a very low incidence, but began to increase on site I in 1992. More than 10 years after planting, the jack pine trees still show resistance to the European race of G. abietina while all the red pines died.